The function of biblical passages used as graves inscriptions found in the Zelów’s necropolis - Balowska, Grażyna (Bohemistyka, 2018)
Graves inscriptions, which are subject of analysis in the present paper, are a basic element of the sepulchral space of the Evangelical Reformed Parish burial ground in Zelów that brings together the descendants of Czech religious emigrants. It is assumed that the tombstone inscription is a linguistic and iconic message with a defined, conventionalized structure, containing both obligatory and optional verbal elements. This analysis will cover non-obligatory verbal elements represented by final formulas in the form of quotations from the Bible, mainly from the Old Testament (passim the Book of Psalms), less frequently from the New Testament (passim the Gospels). Biblical passages testify to the relationship of the deceased and the tombstone’s founder to God; moreover, they express the desire to commune with God and hope for the reward that is the eternal life.